THE INFLUENCES OF A CORE COGNITIVE VULNERABILITY AND CORE SOCIO-EMOTIONAL COMPETENCY FACTORS ON PSYCHOLOGICAL AND ACADEMIC OUTCOMES IN SCHOOL-GOING ADOLESCENTS - KONG SOOK YEE ADELINE (2019)
Bachelor's